EKSISTENSI AGAMA LOKAL PARMALIM Studi Kasus di Nomonatif Pengahayat Nomor Punguan 35 Desa Air Kulim Mandau Bengkalis - Nelita Br Situmorang; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Indonesian state based on God guarantees the freedom of each citizen to profess their own religion. There are six recognized religions in Indonesia, which is being debated is a flow of trust/ religion locally outside the religion is marginalized as experienced by the original religion Batak Parmalim. Fellow group Batak themselves say that the teaching is parbegu ganjang, misguided, incorrect, sipele begu, an abominable act carrier and the allegations that can not be accounted for so that the issue Parmalim get a hard life in the community. To the researchers sought to discover the existence of Parmalim by knowing how Parmalim local religious belief systems and the factors driving exist Parmalim in the Village Air Kulim Mandau Bengkalis with descriptive qualitative method. The results showed a belief system Malim grouped into two parts: (1) the doctrine that governs the relationship with God Debata Mulajadi Nabolon through the rites Mararisabtu, Mardebata, Martutuaek, Pasahat Tondi, Mangan Napaet Sipaha Sada, Sipaha Lima meaningful as thanksgiving and ask for blessings of life that being said through Pelean (offerings). (2) the doctrine that governs human relations as embodied the values, norms and guidelines of life and meaning. The factors that make Parmalim exist is the loyalty of followers Parmalim to keep running its religious activities, use of technology, coordination with the government and the Minister of Religious Affairs. Parmalim local religion is not the religion of wild stands without the knowledge of government and troubling the people, and never disturb public order. This religion is protected by the government of Indonesia, Directorate Faith Against the almighty God and Tradition. Parmalim also registered in the Department of Education No. I.136 / F.3 / N.1.1 / 1980 then duly people began to accept and coexist peacefully.Keywords: Existence, Religion, Parmalim, Batak.